Acid-exposed and hypoxic cancer cells do not overlap but are interdependent for unsaturated fatty acid resources - Katarzyna Głowacka; Sébastien Ibanez; Ophélie Renoult; Perrine Vermonden; Maria Virginia Giolito; Kübra Özkan; Charline Degavre; Léo Aubert; Céline Guilbaud; Florine Laloux-Morris; Elena Richiardone; Jérôme Ambroise; et al. (Nature Communications)
Abstract Cancer cells in acidic tumor regions are aggressive and a key therapeutic target, but distinguishing between acid-exposed and hypoxic cells is challenging. Here, we use carbonic anhydrase 9 (CA9) antibodies to mark acidic areas in both hypoxic and respiring tumor areas, along with an HRE-GFP reporter for hypoxia, to isolate distinct cell populations from 3D tumor spheroids. Transcriptomic analysis of CA9-positive, hypoxia-negative cells highlights enriched fatty acid desaturase activity. Inhibiting or silencing stearoyl-CoA desaturase-1 (SCD1) induces ferroptosis in CA9-positive acidic cancer cells and delays mouse tumor growth, an effect enhanced by omega-3 fatty acid supplementation. Using acid-exposed cancer cells and patient-derived tumor organoids, we show that SCD1 inhibition increases acidic cancer cell reliance on external mono-unsaturated fatty acids, depriving hypoxic cells of essential resources. This bystander effect provides unbiased evidence for a lack of full overlap between hypoxic and acidic tumor compartments, highlighting a rationale for targeting desaturase activity in cancer.